2015
DOI: 10.1007/s10992-015-9374-6
|View full text |Cite
|
Sign up to set email alerts
|

Paths to Triviality

Abstract: This paper presents a range of new triviality proofs pertaining to naïve truth theory formulated in paraconsistent relevant logics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(2 citation statements)
references
References 46 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…366f] showed that any such logic which also has the fusion connective will trivialize all of the mentioned naïve theories. 17 Fusion was therefore not adopted as a logical connective. One may, however, still try to work out a notion of suppression which restricts not only rules on the form B ∧ A → C B → C, but also B → (A → C) B → C. Finding a criterion for which such rules to deem suppressive, will then, just as in the extensional case, be the hard task.…”
Section: Speak Of the Devil And He Doth Appear: The Rhetorics Of Suppmentioning
confidence: 99%
“…366f] showed that any such logic which also has the fusion connective will trivialize all of the mentioned naïve theories. 17 Fusion was therefore not adopted as a logical connective. One may, however, still try to work out a notion of suppression which restricts not only rules on the form B ∧ A → C B → C, but also B → (A → C) B → C. Finding a criterion for which such rules to deem suppressive, will then, just as in the extensional case, be the hard task.…”
Section: Speak Of the Devil And He Doth Appear: The Rhetorics Of Suppmentioning
confidence: 99%
“…See[14, Sec. 9] for a triviality proof using ∀ = BB d strengthened by the rule version of E7.Australasian Journal of Logic (14:1) 2017, Article no.…”
mentioning
confidence: 99%